Performance Improvement Through Teacher Compensation - Lajaria, Ridha Taurisma; Imran; Patulak, Lucia Evianti; Hurlan (International Journal of Management and Education in Human Development, 2023)
This study aims to determine the effect of compensation on the performance of teachers in SMA Negeri 1 Wawonii Tenggara, Konawe Kepulauan Regency. The population in this study were 16 teachers at SMA Negeri 1 Wawonii Tenggara, Konawe Islands Regency. The method of determining the sample in this study used the census method, namely the sampling method with the same sample size as the total population, namely 16 teachers of SMA Negeri 1 Wawonii Tenggara, Konawe Islands Regency. The technique or method of data collection is done by circulating a list of questions (questionnaires) to respondents that have been systematically compiled according to research needs. Data obtained from 16 respondents. Data analysis using simple linear regression. The results of the analysis show that compensation has a significant effect on the performance of teachers at SMA Negeri 1 Wawonii Tenggara, Konawe Islands Regency. The bivariate regression results show the compensation variable has a t-sig value of 0.002, when compared to the 0.05 significance level, the t-sig value (0.002) < α = 0.05 or 5%. This shows that the greater the school provides compensation to the teacher, the teacher's performance at the school will increase.